Role of right ventricular anisotropic viscoelasticity in pathophysiology of RV failure - LeBar, Kristen, author; James, Susan, advisor; Wang, Zhijie, advisor; McGilvray, Kirk, committee member; Chicco, Adam J., committee member; Popat, Ketul, committee member (Colorado State University. Libraries, 2024)
Right ventricular (RV) failure is a key contributor to the mortality and morbidity of multiple cardiovascular diseases, such as congenital heart disease, heart failure with preserved ejection fraction, and pulmonary hypertension (PH). There has still, though, been a lack of treatment for such patients, due largely to a lack of understanding of the pathology and physiology of RV failure. Right ventricular passive stiffness is significantly increased in disease progression, and this change in mechanical behavior have been shown to markedly contribute to RV diastolic and systolic function. However, the myocardium is viscoelastic, and there is both energy storage (elasticity) and dissipation (viscosity) involved in the dynamic deformation within each cardiac cycle. Therefore, the long-ignored viscous component and its impact on organ performance must be investigated. Understanding of the impact of RV viscoelasticity in RV performance will fill a key knowledge gap in RV pathophysiology. Furthermore, the microtubule (MT), a cytoskeletal component of the cardiomyocyte (CM), is known to significantly contribute to the pathophysiology of multiple cardiovascular diseases. In the pressure-overloaded RV, MT density increases, leading to a stiffening of the CM and thus potentially the entire ventricular wall. Moreover, recent cell studies have shown that the pharmaceutical removal of the MT network reduces CM viscoelasticity and increases the extent of shortening, indicating a key role of the MT network myocardial viscoelasticity and contractile function. These findings suggest a regulation of myocardial viscoelasticity and organ contractility via the MT network. Therefore, the overall goal of my study is to determine the contribution of right ventricular anisotropic viscoelasticity to organ function during PH progression. The three specific aims of my dissertation research are: determine the alterations of RV anisotropic viscoelasticity in PH; delineate the contribution of the microtubules network to RV anisotropic viscoelasticity; explore the impact of the RV viscoelasticity on organ function using experimental and computational approaches.
Keywords: cardiovascular sciences; microtubules; pulmonary hypertension; computational modeling; biaxial mechanical test; pressure volume loop